Concentration of metallothionein in the liver of chicken which were given cadmium (Cd) into their feed - ., Darmono; Arifin, Z; Purwadikarta, M.B; Safuani, A; Waznah, U (Indonesian Animal Sciences Society, 2000)
Metallothionein is a metal-binding protein which always detected in the liver of chicken, especially essential element binding protein such as Zn-thionein. Zinc binding protein is usually used for enzyme activity in normal physiology of the animal. The aim of this study was to detect the effect of Cd given into feed on Zn-thionein contain in the liver of broiler chicken. Forty-five broiler chicken were divided into three groups, which was 15 animals in each group. Group 1 as a control group, Group 2 was given 100 mgCd/kg of feed, and group 3 was given 200 mgCd/kg of feed respectively. Body weight of five chicken per group were measured every day and liver samples of five animals per group were collected at day 7 , 14 and 21 after treatment respectively for analysis of Cd and Zn total concentrations and Cd and Zn binding protein. The result indicated that body weight of chicken in the treatment groups were lower than the control group. Zinc binding protein was highest in the control group after 21 days of treatment (2.35 ug/g), but it was low in the two treatment groups were 1.30 and 0.64 ug/g respectively, in which Cd-thionein was formed. On the other hand total Zn concentration were almost similar between treatment, 20.95 ug/g for the control group and 21.24 ug/g for group 2, and 25.37 ug/g for group 3 respectively (P>0.05). It can be concluded that Cd contamination in feed can cause decreased of Zn-thionein within 21 days of treatment, causing retardation of the animals. Â Key words: Cadmium, zinc, metallothionein, liver, chicken, feed